Event-by-event Hydrodynamics for LHC - Machado, Meera Vieira (2015)
We perform an event-by-event hydrodynamic analysis for Pb-Pb collisions at the incident energy of sqrt(sNN) = 2.76TeV, also studying the effects of two equations of state under the same initial conditions and freeze-out scenario: one characterized by a critical point and the other based on Lattice QCD (Quantum Chromodynamics) calculations. The observables of interest are particle spectra in terms of pseudorapidity and transverse momentum, as well as flow harmonics, which are coefficients that carry information on the initial anisotropies of the system throughout its evolution. Those are computed and compared with experimental Large Hadron Collider (LHC) data. There are slight differences in the results for each equation of state, caused by their distinct features. Lastly, the LHC-based calculations are compared with previous works related to the Relativistic Heavy-Ion Collider (RHIC) experimental data. The main techniques of the latter are performed in this work, which results in differences between some aspects in the outcome for each collision type, from initial energy distributions to freeze-out temperatures.